Numerical Investigation of Flow around Two Tandem Identical Trapezoidal Cylinders. (27th April 2020) - Wang, Yupu; Cheng, Wenming; Du, Run; Wang, Shubiao; Deng, Yong
Abstract : The trapezoidal beam structure is ubiquitous in giant engineering equipment, while their aerodynamic characteristics have not been clearly understood. Numerical simulation method was adopted to investigate the flow around two tandem identical trapezoidal cylinders. The study was conducted using a Reynolds number of 2.2 × 10 4, and with a spacing ratio varying from 0.5 to 10. The incompressible two-dimensional finite volume method was used for solving Reynolds-Averaged Navier–Stokes (RANS) equations with realizable k − ε model. The effects of cylinder geometry and spacing between the cylinders on aerodynamic characteristics, unsteady flow patterns, time-averaged flow characteristics, and flow instability was studied. The results show that the flow around the two tandem trapezoidal cylinders is highly dependent on the spacing ratio. The flow modes can be classified into: extended-body regime (Mode I, S ∗ ≤ 1), reattachment regime (Mode II, 2 ≤ S ∗ ≤ 3), and binary regime (Mode III, S ∗ ≥ 4). We explored their respective flow characteristics and distinctions through the force/pressure coefficients, time-average streamwise velocity, and the flow field evolution.